Validity and Reliability of the International Fitness Scale (Ifis) in Preschool Children - Garcia-Hermoso, A (Taylor and Francis Ltd., 2023)
Objectives: Examine the validity and reliability of parent-reported International FItness Scale (IFIS) in preschoolers. Method: A cross-sectional study of 3051 Spanish preschoolers (3–5 years). Fitness was measured by PREFIT battery and reported by parents using an adapted version of the IFIS. Waist circumference was evaluated, and the waist-to-height ratio (WHtR) was calculated. Seventy-six parents of randomly selected schoolchildren completed the IFIS twice for a reliability assessment. Results: ANCOVA, adjusted for sex, age and WHtR, showed that preschoolers who were scored by their parents as having average-to-very good fitness had better levels of measured physical fitness than those preschoolers who were classified as having “very poor/poor” fitness levels (18.1laps to 22.1laps vs 15.6laps for cardiorespiratory fitness; 6.6 kg to 7.5 kg vs 5.3 kg for muscular fitness-handgrip-; 71.7 cm to 76.4 cm vs 62.0 cm for muscular fitness-standing long jump-; 17.2s to 16.2s vs 18.2s for speed/agility; and 11.2s to 15.6s vs 8.7s for balance; p < 0.001). The weighted kappa for concordance between parent-reported fitness levels and objective assessment was poor (κ ≤ 0.18 for all fitness measures). Overall, the mean values of the abdominal adiposity indicators were significantly lower in high-level fitness categories reported by parents than in low-level fitness categories (p < 0.05). The test-retest reliability ranged from 0.46 to 0.62. Conclusions: The reliability of the parent-reported IFIS are acceptable, but the concordance between parents reported and objectively measures fitness levels is poor, suggesting that parents’ responses may not be able to correctly classify preschoolers according to their fitness level. Highlights The convergent validity and reliability (test-retest) values of the IFIS parent scale are moderately acceptable for assessing physical fitness in children aged 3–5 years. However, the results of concordance show that criterion validity is poor suggesting that parents’ responses may not be able to correctly classify preschoolers according to their fitness level. Considering that the fitness level at these ages is fairly homogeneous, it seems difficult for parents to discriminate between the fitness levels of their children. Therefore, it seems necessary to recalibrate the scale in future work. © 2022 European College of Sport Science.